Techno-Economic on the Production of Aromatherapy Candles from Aetheric Oils - Andre Safrie Maulana (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
The waste produced by oranges is orange peel which is still abundant, so making aromatherapy candles can have a good effect on the environment. This research aims to analyze the feasibility of a project to produce aromatherapy candles from aetheric oils on a large scale. Evaluation from an engineering perspective is determined by the evaluation of the initial factory design and stoichiometric calculations. Meanwhile, the evaluation from an economic perspective is determined by several parameters, such as Payback Period, Gross Profit Margin, Cumulative Net Present Value, etc. Based on the results of the analysis, the aromatherapy candle production project from aetheric oil can be scaled to industrial level and demonstrate a profitable project from a technical and economic perspective. This project also helps waste from sweet oranges (citrus sinensis), so that it can have a good effect on the environment and reduce accumulated waste. Based on this, this project is an innovative project so that it can compete with market standards. From the results of the economic evaluation analysis it can be concluded that this project is feasible to carry out.